Treadmill Exercise During Cerebral Hypoperfusion Has Only Limited Effects on Cognitive Function in Middle-Aged Subcortical Ischemic Vascular Dementia Mice - Ohtomo, Ryo; Ishikawa, Hidehiro; Kinoshita, Keita; Chung, Kelly K.; Hamanaka, Gen; Ohtomo, Gaku; Takase, Hajime; Wrann, Christiane D.; Katsuki, Hiroshi; Iwata, Atsushi; Lok, Josephine; Lo, Eng H.; et al. (Frontiers in Aging Neuroscience, 2021)
Clinical and basic research suggests that exercise is a safe behavioral intervention and is effective for improving cognitive function in cerebrovascular diseases, including subcortical ischemic vascular dementia (SIVD). However, most of the basic research uses young animals to assess the effects of exercise, although SIVD is an age-related disease. In this study, therefore, we used middle-aged mice to examine how treadmill exercise changes the cognitive function of SIVD mice. As a mouse model of SIVD, prolonged cerebral hypoperfusion was induced in 8-month-old male C57BL/6J mice by bilateral common carotid artery stenosis. A week later, the mice were randomly divided into two groups: a group that received 6-week treadmill exercise and a sedentary group for observation. After subjecting the mice to multiple behavioral tests (Y-maze, novel object recognition, and Morris water maze tests), the treadmill exercise training was shown to only be effective in ameliorating cognitive decline in the Y-maze test. We previously demonstrated that the same regimen of treadmill exercise was effective in young hypoperfused-SIVD mice for all three cognitive tests. Therefore, our study may indicate that treadmill exercise during cerebral hypoperfusion has only limited effects on cognitive function in aging populations.